Paving the way : the first American women law professors - Kay, Herma Hill (Law in the public square, 2021)
"When it comes to breaking down barriers for women in the workplace, Ruth Bader Ginsburg's name speaks volumes for itself-but, as she clarifies in the foreword to this long-awaited book, there are too many trailblazing names we do not know. Herma Hill Kay, former Dean of UC Berkeley School of Law and Ginsburg's closest professional colleague, wrote Paving the Way to tell the stories of the first fourteen female law professors at ABA- and AALS-accredited law schools in the United States. Kay, who became the fifteenth such professor, labored over the stories of these women in order to provide an essential history of their path for the more than 2,000 women working as law professors today and all of their feminist colleagues. Because Herma Hill Kay, who died in 2017, was able to obtain so much first-hand information about the fourteen women who preceded her, Paving the Way is filled with details, quiet and loud, of each of their lives and careers from their own perspectives. Kay wraps each story in rich historical context, lest we forget the extraordinarily difficult times in which these women lived. Paving the Way is not just a collection of individual stories of remarkable women but also a well-crafted interweaving of law and society during a historical period when women's voices were often not heard and sometimes actively muted. The final chapter connects these first fourteen women to the "second wave" of women law professors who achieved tenure-track appointments in the 1960s and 1970s, carrying on the torch and analogous challenges. This is a decidedly feminist project, one that Justice Ruth Bader Ginsburg advocated for tirelessly and admired publicly in the years before her death"--